A mini-review on bio-inspired polymer self-assembly: single-component and interactive polymer systems. Issue 6 (22nd December 2022) - Meng, Xiangxi
Abstract : Biology demonstrates meticulous ways to control biomaterials self-assemble into ordered and disordered structures to carry out necessary bioprocesses. Empowering the synthetic polymers to self-assemble like biomaterials is a hallmark of polymer physics studies. Unlike protein engineering, polymer science demystifies self-assembly by purposely embedding particular functional groups into the backbone of the polymer while isolating others. The polymer field has now entered an era of advancing materials design by mimicking nature to a very large extend. For example, we can make sequence-specific polymers to study highly ordered mesostructures similar to studying proteins, and use charged polymers to study liquid–liquid phase separation as in membraneless organelles. This mini-review summarizes recent advances in studying self-assembly using bio-inspired strategies on single-component and multi-component systems. Sequence-defined techniques are used to make on-demand hybrid materials to isolate the effects of chirality and chemistry in synthetic block copolymer self-assembly. In the meantime, sequence patterning leads to more hierarchical assemblies comprised of only hydrophobic and hydrophilic comonomers. The second half of the review discusses complex coacervates formed as a result of the associative charge interactions of oppositely charged polyelectrolytes. The tunable phase behavior and viscoelasticity are unique in studying liquid macrophase separation because the slow polymer relaxation comes primarily from charge interactions. Studies of bio-inspired polymer self-assembly significantly impact how we optimize user-defined materials on a molecular level.